Pengaruh Sikap Religiusitas dan Keaktifan Belajar terhadap Hasil Belajar pada Peserta Didik SMK Negeri 1 Jambu dan SMK Roudlotul Furqon Kabupaten Semarang - Indrawan, Prydar Sakti; Winarno, Winarno (Attractive : Innovative Education Journal, 2022)
The article was to analyze the effect of religious attitudes, to analyze the effect of active learning, to analyze the attitude of religiosity and learning activity on students learning outcomes at SMK Negeri 1 Jambu and at SMK Roudlotul Furqon, Kebumen Banyubiru, Semarang Regency. It used quantitative research. The data collection method used survey methods, quantitative or statistical data analysis, with the aim of applying for hypotension that has been determined. The total sample was 75 students. The test instrument used is a test of validity and reliability. Data analysis used multiple linear regression, F test and t test. The results show that: based on the output table of the first Summary Model, was known that the coefficient of R Square was 0.429 or equal to 42.9%, then the variable of religiosity (X1) has an effect on stu’dents learning outcomes (Y) of 42.9%. While the remaining 100% - 42.9% = 57.1% influenced by other variables not examined. Based on the output table of the second Summary Model, it was known that the R Square coefficient was 0.420 or equal to 42.0%. Hence, the learning activity variable (X2) has an effect on students’ learning outcomes (Y) by 42.0%. While the remaining 100% - 42.0% = 58.0% was influenced by other variables not examined. Based on the output table of the third Summary Model, was known that the R Square value 0.632 or equal to 63.2%, meaning that the variables of religious attitudes (X1) and learning activity (X2) simultaneously affect PAI learning outcomes (Y), which were 42, 0%. While the remaining 100% - 63.2% = 36.8% influenced by other variables not examined. Keywords: Religious Attitude, Learning Activity, Learning Outcome